The formulas for the representation of functions of two variables as a difference of sublinear functions. (3rd October 2019) - Grzybowski, Jerzy; Pallaschke, Diethard; Urbański, Ryszard
ABSTRACT: Having a function being a difference of sublinear functions defined on a plane, we present a formula for effective calculation of sublinear functions such that their difference is equal to the given one. Moreover, these newly calculated sublinear functions are minimal and as such unique-up-to-linear-summand. We also provide examples of such functions.